Ultimate nachos : from nachos and guacamole to salsas and cocktails - Frank, Lee, 1984- (St. Martin's Griffin, 2013)
"Nachos are the ultimate comfort food and the extreme guilty pleasure. As the team behind Nachos NY, authors Lee Frank and Rachel Anderson have set off on a mission to reinvent the nacho and elevate it from it's status as neon-yellow-cheese-smothered bar food to delectable gooey treats to dig into and share with friends. As Nachos NY, Frank and Anderson have put their extensive nacho knowledge to work to show off the flexibility of this popular snack with eighty-four creative recipes that are inspired by comfort foods and international flavors that everybody loves. From Fried Calamari Nachos to Croque Monsieur Nachos; Philly Cheesesteak; Roasted Beet, Apple, and Goat Cheese; Pork Ginger; and even Poached Pear and Gorgonzola Dessert Nachos--this book will have you crunching down on sweet and savory nachos all year round at backyard bbqs, on Super Bowl Sunday, or for dinner with the family. And, of course, nachos aren't complete without salsa, guacamole, and queso. A range of sauces to dip into and drizzle on to your chips are provided, including Clementine Pico de Gallo, Bacon Apple Guac, Mango Chipotle Sauce, and much more! Then pair your dish with the complementary drink recipes for margaritas, horchata, and sangria and throw yourself a real fiesta! "--